Konsep Tri Hita Karana Dalam Pelaksanaan Pariwisata Budaya Hindu - I Wayan Sudiarta (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Tourism has a wide reach that concerns the interests of society as a whole, so it must be implemented properly. In Bali in general, in the implementation of tourism and its management with a cultural concept, it is necessary to make efforts to manage, preserve and develop assets owned by the region, especially cultural heritage which makes the objects and attractions of such cultural tourism. For this reason, it is necessary to manage cultural heritage that can organize and promote cultural heritage that can preserve cultural heritage. The island of Bali in the field of tourism offers many things for tourists to enjoy, not only its beautiful and captivating nature, but also cultural tourism which is a cultural-based characteristic in Bali which is important for tourists to know and enjoy. . In the development and application of culture, many concepts are carried out by tourism developers, ranging from local wisdom to following existing developments. In Hindu local wisdom, the concept that can be applied in the development of Hindu cultural tourism is the Tri Hita Karana Concept. The term Tri Hita Karana is developing, developing and socializing. In the concept of Hindu community life, Tri Hita Karana is the concept of balance, harmony and harmony between bhuana agung and bhuana alit which in its implementation emphasizes the harmonious relationship between humans and God / Ida Sang Hyang Widhi Wasa, humans and humans, and humans and the environment. The Tri Hita Karana concept in organizing Hindu cultural tourism is a concept that directs besides tourism development it can also protect ancestral heritage that has existed for a long time. The purpose of this paper is to find out about the Tri Hita Karana concept in the implementation of Hindu cultural tourism. The data collection method used in the writing of this article is the method of recording documents or literature study. As well as data analysis using descriptive analysis methods with induction and argumentation techniques. The results obtained from the writing of this scientific article are that the Tri Hita Karana Concept can be described in the implementation of Hindu cultural tourism. Besides that, you can find out how to maintain the existence and maintain the sacredness of the holy place in the Parhyangan Tri Hita Karana section.Keywords: Tri Hita Karana Concept and Hindu Cultural Tourism